Towards a Theoretical Framework for the Assessment of the Marine Living Resources (MLR) Legislative Framework of South Africa: Implications for Effectively Regulating Harvesting of MLR Such as Wild Abalone (Haliotis midae) - Cliff Sibusiso Dlamini (Challenging Issues on Environment and Earth Science Vol. 1, 2021)
This is a brief study of existing legislative frameworks for fisheries in South Africa. The study assesses the different marine legislative frameworks and ascertain how such laws contributes towards the effective management of fisheries in South Africa. The main focus is on endangered marine species, particularly abalone. The Marine Living Resources Act (MLRA) of South Africa was enacted in 1998 with the main objective of protecting the countries marine fisheries including endangered species. Since then, the country has developed policies and acts meant to strengthen the MLRA. Such policies includes the policy for the Small Scale Fisheries Sector (SSFP) in South Africa which was enacted in 2012. The Marine Living Resources Amendment Act, Act no. 5 of 2014, was passed in May 2014 to strengthen the MLRA and allow for the implementation of the SSFP. The implementation of the MLRA and its supporting policies is driven by the need to achieve marine resource sustainability, encourage economic growth within the marine industry and protect endangered marine life through implementation of anti- poaching legislation and ensuring marine pollution is minimized. South Africa has faced a series of challenges in implementing these objective and so far most of the initiatives are not implemented effectively. A group of fishers (subsistence and artisanal fishers) have remained marginalized and overlooked in the fishing rights allocation process despite regulations being put in place to support such initiative. However, there is hope for small scale fisheries given that the government envisage adopting a community-based, co-management approach which will see fishing rights allocated to small-scale fishing communities and these communities co-managing fisheries together with government.